2008
DOI: 10.1108/13527600810848854
|View full text |Cite
|
Sign up to set email alerts
|

Are managerial gender stereotypes universal?

Abstract: Purpose -The purpose of this paper is to compare the extent to which the stereotype of ''manager'' aligns with the stereotype of ''male'' in the Continental United States (CUS) and Hawai'i. Design/methodology/approach -In total, 176 male and 187 female business undergraduates in Hawai'i and the CUS were asked to describe either a manager, a male manager, or a female manager using the 92-item Schein Descriptive Index. Findings -Men and women in Hawai'i, and women in the CUS, did not report a strong ''think mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This research design is a replication of the original Schein (1973) and subsequent studies (Brenner et al , 1989; Heilman et al , 1989; de Pillis et al , 2008; Dodge et al , 1995; Schein et al , 1989, 1996). A replication approach was used in order to allow for comparison of findings to Schein's original studies and the results of the subsequent research performed in eight other countries.…”
Section: Methodsmentioning
confidence: 99%
“…This research design is a replication of the original Schein (1973) and subsequent studies (Brenner et al , 1989; Heilman et al , 1989; de Pillis et al , 2008; Dodge et al , 1995; Schein et al , 1989, 1996). A replication approach was used in order to allow for comparison of findings to Schein's original studies and the results of the subsequent research performed in eight other countries.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents in her study were asked to characterize whether the traits were more closely related to "men in general", "women in general", or "successful middle manager". The original Schein (1973Schein ( , 1975 studies along with extensive use of the Schein Descriptive Index by other researchers have found, with few exceptions (Booysen and Nkomo, 2010;dePillis et al, 2008;Duehr and Bono, 2006;Schein, 2007), that successful middle managers are perceived as possessing characteristics, temperaments, and attitudes that were more commonly ascribed to men in general than to women in general (Gorman, 2005;Schein, 1973Schein, , 1975Schein, , 1994Schein and Mueller, 1992;Schein et al, 1989; Sex role stereotypes Brenner et al, 1989;Bass, 1990). Studies using different methodologies and instruments have produced similar results (Eagly and Karau, 2002;Heilman, 1984Heilman, , 2001Powell and Butterfield, 1979).…”
Section: Women and Managerial Stereotypesmentioning
confidence: 99%
“…Research using male and female business students in Hawaii also highlights this premise. When students belong to a culture that includes women in leader positions, they are less likely to hold "think-manager-think-male" stereotypes (dePillis et al, 2008). To determine if familiarity with diversity and females in the managerial role actually decreases sex role stereotypes, we test three groups of university students with varying levels of exposure to formal business education to determine how they perceive gender and managerial characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Fullagar et al (2003) examined the "think manager-think male" phenomenon in Turkey and Sweden and found that both men and women reported that successful managers possessed characteristics and attitudes more commonly ascribed to men than women. de Phillis et al (2008) found that both men and women in Hawai'i and women in the Continental United States did not have a strong "think manager-think male" bias, but men in the Continental United States did. Booysen and Nkomo's (2010) study in South Africa was one of the first studies to examine the combined effect of race and gender on the "think manager-think male" phenomenon.…”
Section: Prior Researchmentioning
confidence: 99%